Diseño de un sistema de control interno en la plantación Eastman Pérez Cia. Ltda. Ubicada en la provincia de Cotopaxi, cantón Latacunga - Pincha Vargas, Sonnia Patricia (2011)
Internal control is an organizational plan that has with objective to safeguard and preserve the goods of the company, through methods and procedures to prevent inadequate expenditure of funds and provide security that compliance with policies and regulations that have the institution. The Greenhouse "Eastman Perez" Cia. Ltda. In the actuality, it does not have with an Internal Control System to develop in the appropriate way each activities and functions by workers. Also it does not have an adequate segregation of function that can facilitate to take the correct decision since. It cannot fulfill with emphasis each policy and standards established within the greenhouse, so that there will be greater customer satisfaction and achieve the goals set by the organization. And the present investigation will be developedment in order to provide the institution functions and procedures that will help to achieve greater efficiency, effectiveness, economy and usefulness in both administrative and operational activities will be performed in the greenhouse. In conclusion, the internal control system will allow to the staff from the greenhouse to carry out all functions and tasks assigned to each one.